Sibār/Sippar [in Latin Characters]/ UD.KIB.NUN.KI [in Cuneiform], 2. 'aḥdāt min ta'rīḫ al-madīnah ('Abū Ḥabbah) - al-Ğādir, Walīd M. (1988)
New Information on the History of the City of Sippar (Abu Ḥabbah); no ISBN; in Arabic